2020
DOI: 10.1007/s42399-020-00415-9
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Neuralgia: Etiology, Diagnosis, and Treatment

Abstract: Trigeminal neuralgia (TN), the most common of the facial neuralgias, is an extremely debilitating disorder that is characterized by severe electric shock-like neuropathic pain that is localized to one or more branches of the trigeminal nerve. It can have a serious impact on an individual's life and is often first encountered by dentists and general practitioners. Although a treatable and usually manageable condition, appropriate diagnosis remains a factor that plagues this disease. The objective of this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The main cause for TN is the compression of the 5th cranial nerve, which contains 3 major branches that control the motor functions of the face (37). However, the pathogenesis of TN is not completely clear (38,39). Due to the severe pain, TN often has a catastrophic effect on patients, and seriously affects their quality of life (40).…”
Section: Discussionmentioning
confidence: 99%
“…The main cause for TN is the compression of the 5th cranial nerve, which contains 3 major branches that control the motor functions of the face (37). However, the pathogenesis of TN is not completely clear (38,39). Due to the severe pain, TN often has a catastrophic effect on patients, and seriously affects their quality of life (40).…”
Section: Discussionmentioning
confidence: 99%
“…Silvia et al [ 8 ], provide excellent insights regarding the treatment of TN and highlight the need for improvement and updates in the management of TN; as an estimated 50% of patients fail to achieve complete pain relief with medico/pharmacological options and ultimately opt for surgical interventions. Meta-analyses have reported that microvascular decompression (MVD) was the most efficacious surgical treatment for classical TN caused by trigeminal nerve compression by a branch of the basilar artery which provides pain relief for 4–5 years in 61 to 80% patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%